2017
DOI: 10.1021/acs.orglett.7b01942
|View full text |Cite
|
Sign up to set email alerts
|

Co(II)-Catalyzed Regioselective Cross-Dehydrogenative Coupling of Aryl C–H Bonds with Carboxylic Acids

Abstract: A cobalt(II)-catalyzed regioselective aryl C−H bond oxygenation between arenes and aryl or aliphatic carboxylic acids under bidendate-chelation assistance is developed. This method provides an efficient approach to acyoxy-substituted arenes with a broad range of functional group tolerance. Furthermore, this reaction system could be further applied to the preparation of polyfunctional naphthylenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 39 publications
0
26
0
Order By: Relevance
“…In 2017, Zeng reported a Co-catalysed cross dehydrogenative coupling (CDC) between picolinamide derivatives with aliphatic and aromatic carboxylic acids ( Scheme 95C ). 573 It is worth mentioning that this transformation was mainly restricted to naphthalene compounds and only two N -benzyl substituted 2-pyridinecarboxamides were functionalised as well, although in low yields (25 and 37%). Acetoxylation at the remote ε-C(sp 2 )–H bond was studied by Babu using this bidentate DG (not shown).…”
Section: Bidentate Dgsmentioning
confidence: 99%
“…In 2017, Zeng reported a Co-catalysed cross dehydrogenative coupling (CDC) between picolinamide derivatives with aliphatic and aromatic carboxylic acids ( Scheme 95C ). 573 It is worth mentioning that this transformation was mainly restricted to naphthalene compounds and only two N -benzyl substituted 2-pyridinecarboxamides were functionalised as well, although in low yields (25 and 37%). Acetoxylation at the remote ε-C(sp 2 )–H bond was studied by Babu using this bidentate DG (not shown).…”
Section: Bidentate Dgsmentioning
confidence: 99%
“…Very recently, cobalt catalysis assisted by bidentate directing groups was also applied in C−H bond activation reactions to realize a variety of useful transformations . Inspired by the above encouraging achievements and our continuing endeavors on transition metal‐catalyzed directed C−H bond functionalization, we are intrigued by the cobalt‐catalyzed acyloxylation reaction of arenes and alkenes with readily accessible carboxylic acids . It was observed that the direct acyloxylation of arenes and alkenes could be realized with the assistance of an 8‐aminoquinolyl auxiliary to lead to the corresponding esters in high yields.…”
Section: Introductionmentioning
confidence: 99%
“…Wu's group reported a palladium‐catalyzed acylation of naphthylamines with acyl chlorides . In 2017, Zeng's group demonstrated a cobalt‐catalyzed coupling of naphthylamines with carboxylic acids . These two methods offers an easy access to 1,8‐disubstitued naphthalenes which could be further functionalized.…”
Section: C8‐functionalization Of Naphthalene Derivativesmentioning
confidence: 99%